West Greenland's Cod-to-Shrimp Transition : Local Dimensions of Climatic Change - Hamilton, Lawrence C.; Brown, Benjamin C.; Rasmussen, Rasmus Ole (ARCTIC, 2003)
West Greenland's transition from a cod-fishing to a shrimp-fishing economy, ca. 1960-90, provides a case study in the human dimensions of climatic change. Physical, biological, and social systems interacted in complex ways to affect coastal communities. For this integrated case study, we examine linkages between atmospheric conditions (including the North Atlantic Oscillation), ocean circulation, ecosystem conditions, fishery activities, and the livelihoods and population changes of two West Greenland towns: Sisimiut, south of Disko Bay, and Paamiut, on the southwest coast. Sisimiut prospered as a fishing center through the cod-to-shrimp transition. Paamiut, more specialized in cod fishing, declined. Their stories suggest two general propositions about the human dimensions of climatic change. First, socially important environmental changes result not simply from climatic change, but from interactions between climate, ecosystem, and resource usage. Second, environmental changes affect people differentially and through interactions with social factors. Social networks and cohesion (social capital) are important, in addition to skills (human capital), investments (physical capital), and alternative resources (natural capital): all shape how the benefits and costs are distributed. Dans l'ouest du Groenland, la transition de l'économie morutière à l'économie crevettière, qui s'est effectuée à peu près de 1960 à 1990, offre une étude de cas pour la dimension humaine du changement climatique. Des interactions complexes entre les systèmes physique, biologique et social ont eu des répercussions sur les communautés côtières. Pour cette étude de cas intégrée, on examine les liens entre les conditions atmosphériques (y compris l'oscillation nord-atlantique), la circulation océanique, les conditions de l'écosystème, les activités de pêche ainsi que les changements dans le mode de subsistance et la démographie de deux villes du Groenland occidental: Sisimiut, au sud de la baie de Disko, et Paamiut, sur la côte sud-ouest. ...